Influence of Multimedia Learning Mathematics Math-tainment Against Mathematics Student Learning Outcomes - chaerunisa Pujiawat (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2016)
Mathematics learning process is less attractive due to the monotony of learning is dominated by the teacher resulted in students becoming bored and less interested in studying mathematics, the underlying idea of this research. This problem requires a solution that is appropriate to make learning enjoyable so that learning objectives can be achieved. The purpose of this study are: 1) to assess student learning outcomes with the use of multimedia learning mathematics-tainment with learning conventional ; 2) to determine students` response to the use of multimedia learning math mathematics-tainment; and 3) to determine how much influence the use of multimedia learning math mathematics-tainment on the results of students` mathematics learning. The method used in conducting this research is true experimental method experimental design (Experimental real) with the design of the study-control group pre test post test. The technique of collecting data using questionnaires and tests. The results showed that the average percentage of the value of the questionnaire was 75,35%. The regression equation Y Ì‚=1,78 X, this means that from the equation that each additional (increased) use of multimedia learning math mathematics-tainment will affect students` mathematics learning outcomes by 1,78. After testing the hypothesis in mind that t count (11,702) > t table (1,63). Thus the hypothesis is accepted which means there influence of multimedia mathematics learning of math-tainment on the results of students` mathematics learning with a determination coefficient of 47,4%, while the remaining 52,6% is determined by other factors.